FINITE ELEMENT MODELING AND ANALYSIS OF A PASSENGER CAR TYRE - S. Muthuselvi,Dr.kishore brahma , M. Ramesh Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Tyre analyses done through experimental methods takes more time as well as cost and also the development of the new tyre take longer time. To avoid this tidious tyre development process its behaviour can be predicted through Finite Element analysis. The main objective of the work is to perform finite element analysis of the tyre using Abaqus software. For the analysis I had chosen 165/70R 14 81S passenger car tyre and Mooney rivilin material model is used For my analysis. I had used frequency linear perturbation procedure and subspace Eigen solver with the maximum frequency of 20.68 Hz considering the tyre rotates at a speed of 120 Km/hr totally 4000 iteration has been used for this analysis. Since tyre is in torus in shape Tetrahedral element can only used for meshing.From this analysis we can find six different modes of shape of the tyre and maximum displacement at different modes. In static and dynamic analysis I have planned to find out the stress developed in bead part, body ply and tread part